The level of anxiety in learning english as a second language among students of the Mengubah Destini Anak Bangsa (MDAB) Programme in Universiti Teknologi MARA / Kamisah Ariffin, Norzie Diana Baharum and Nor Lailatul Azilah Hamdzah - Ariffin, Kamisah; Baharum, Norzie Diana; Hamdzah, Nor Lailatul Azilah (2011)
Anxiety is considered as one of the affective factors in second language learning. Empirical research has shown that anxiety can play both facilitative and debilitative roles in language learning. This paper reports a pilot study that examines the level of anxiety among the students of the Mengubah Destini Anak Bangsa (MDAB) programme in Universiti Teknologi MARA, the majority of whom came in only with a D score in English in the SPM examination. Such low score has created anxiety in classroom learning as they have to cope with the English language learning environment in the university. Using the Foreign Language Classroom Anxiety Scale (FLCAS) as a framework, the study examined the students' anxiety under four categories: I) fear of negative evaluation, 2) communication apprehension, 3) test anxiety, and 4) anxiety of English Class. The results indicate that the students' anxiety level is rather significant with fear of negative evaluation being the highest. The findings can provide understanding on the learners' anxiety that can militate against their learning success. Informed classroom instructors will be able to help students reduce their anxiety by offering some coping strategies and providing more supportive classroom environment for them.